Rediscovering pneumatology in the "Age of the Spirit": A North American Lutheran contribution. Issue 2 (30th May 2019) - Peterson, Cheryl M.
Abstract: This essay explores Luther's pneumatology, especially in his sermons on the Gospel of John, might offer resources for "discerning the spirits" in the emerging "age of the Spirit, " as Harvey Cox and Phyllis Tickle have dubbed it, which sees the rise of the "spiritual but not religious" and movements calling for spiritual revolution. The author shows that Luther's insistence that the Spirit work through the given means of "Word and sacrament, " was not intended to limit the Spirit's activity in the world, but rather to protect God's people from those who would wish to use the Spirit for their own means and power.